Final Evaluation Report - “Improving oversight in Mozambique's governance” (2016-2019) - FCG International Ltd (FCG International Ltd, 2019)
An external evaluation of the project was conducted in April - May 2019. It looked into the strategy, performance and attainment of the general development goals. The results of the evaluation will be taken into account in the planning of a possible second phase of the project. According to the evaluation, the project is highly relevant both for the strategic partnership between Finland and Mozambique, as well as for the sustainability and inclusiveness of the economic growth arising from the extractive industries and the development of democratic governance. Finnish discretionary government transfers are used to support the Improving Oversight in Mozambique’s Governance 2016–2019 project, which aims to strengthen parliamentary oversight of the management of natural resources in Mozambique. It is a joint project of three organisations; Netherlands Institute for Multiparty Democracy (NIMD), Political Parties of Finland for Democracy (Demo Finland) and Instituto para Democracia Multipartidária from Mozambique (IMD). The project was launched in Mozambique in 2017 and it will be closed at the end of 2019; with a budget of EUR 1,500,000. The evaluation emphasises that strengthening parliamentary oversight is a long-term objective. The project has managed to reach preliminary results in a short time frame in that, for example, Members of Parliament have a better understanding of the challenges met by the extractive industries, and for the first time in Mozambique, there is regular exchange of information and cooperation between national and provincial parliaments. However, performance is not on a sustainable foundation. Sustainable impacts require that a greater number of MPs are trained and the training and research centre of Parliament and the technical secretariats of the provincial parliaments are strengthened. In addition to capacity building, the Parliament should be strengthened by creating wider partnerships and networks with other actors in society. In order to consolidate the results of the project and to improve their sustainability, the evaluation strongly recommends the Ministry for Foreign Affairs to continue the project in cooperation with the new Parliament, which will be elected in October 2019, and with provincial parliaments. It would be useful for the new MPs starting their work at the beginning of 2020 that they make use of the materials produced during the project and consult the MPs who were trained during the project. Additionally, the evaluation recommends the Ministry for Foreign Affairs to continue the project with the same partners, because they have managed to establish well-functioning and confidential relations with the Parliament and other political actors.
Keywords: *tagged; G - Mozambique / Moçambique; L - english / inglês; M - evaluation / avaliação; citizenship & participation / cidadania e participação; decentralization / descentralização; governance / governação

Implement - Outcome Harvesting|Civicus - CIVICUS (CIVICUS, 2019)
Outcome Harvesting is a M&E methodology used to identify, describe, verify and analyses the changes brought about by a campaign, support or advocacy initiative (see Better Evaluation or Winter School 2019 presentation by Outcome Mapping Learning Community). In Outcome Harvesting, one collects evidence of change (‘outcomes’ – e.g. changed policy, amended or stopped legislation processes, a new coalition formed, shifted voting behaviour) and then works backwards to assess contribution to that change. Please note that the change can also be a negative change, and/or the change cannot be linked to one’s own contributions but rather to those of other actors. It may be referred to as Outcome Mapping methodology. However, in Outcome Harvesting, there are also other methodologies used during the harvest process. Outcome harvesting can be used for ongoing monitoring throughout a project or programme, in order to produce real-time information on change. It can also be used with evaluation or impact assessments during projects or programmes, at the end of a project, or some time after they have been completed. Outcome Harvesting involves participation with different stakeholders. According to Wilson-Grau (2015) participation is described by the methodology’s main developer as necessary for a successful outcome harvesting process and product. Moreover, it is considered most useful under three conditions (see Ricardo Wilson-Grau and Heather Britt 2012): Focus on outcomes rather than activities: It is not designed to assess whether activities were carried out according to plan, rather than assessing what has changed and why. Complex programming contexts: Outcome Harvesting is suitable for complex programming context where the relationship between the cause and the effects is not fully understood. Examples of complex situations could include in areas such as advocacy, mobilization, capacity development, empowerment or network development. Monitoring and evaluation: Outcome Harvesting can also be used when the purpose as an M&E exercise is to learn about the change and understanding why those changes occurred.
Keywords: *tagged; L - english / inglês; M - evaluation / avaliação; M - methodology / metodologia

Managing for Sustainable Development Impact - Kusters, Cecile; Batjes, Karen; Wigboldus, Seerp; Brouwers, Jan; Baguma, Sylvester Dickson (Practical Action Publishing Ltd, 2017)
This guide is about managing development initiatives and organizations towards sustainable development impact. It builds on the work of Guijt and Woodhill in the 2002 IFAD publication Managing for Impact in Rural Development: A Guide for Project M&E. Since then, the managing for sustainable development impact (m4sdi) approach has evolved with insights and feedback from CDI colleagues, clients, partners, and over 800 people who have been trained in its use. In addition, the authors have drawn on the work of many others. m4sdi is an integrated, results-oriented management approach, which can be used across a range of sectors and domains in a variety of contexts, and aims to contribute towards the Sustainable Development Goals (SDGs). It seeks to integrate ideas and practices from a range of approaches and methodologies for planning, monitoring and evaluation, using appropriate methods or tools that engage people in a process of learning and adaptation. It is specifically aimed at strengthening the readiness of leaders, decision-makers and development practitioners to effectively manage their initiatives/organizations in complex settings. m4sdi belongs to a special niche of management approaches, providing relevant perspectives on what makes for effective management for those directly involved in managing initiatives/organizations and wider groups of stakeholders. Many of the people trained in m4sdi have become believers and practitioners of the approach because it addresses several of the most serious concerns in development, such as the difficulty in reaching primary stakeholders, designing effective strategies and related monitoring and evaluation (m&e), focusing on capacity development and change management, and achieving sustainable development impact. The strength of m4sdi lies in its people-centred approach and how it seeks to integrate management processes within a complex environment. The evolvement of the approach needs to be documented to share lessons learned and support capacity development. And so the principles and practices covered in this guide relate to a variety of development initiatives/organizations in the fields of agriculture, food security, local economic development, value chains, enterprise development, and ecosystem governance. Much of the discussion takes place within the often complex context of development. As such, the guide aims to find a good balance between comprehensiveness and the principle of ‘less is more’.
Keywords: *tagged; L - english / inglês; M - evaluation / avaliação; M - methodology / metodologia

Country Evaluation Brief - Mozambique - CMI (Chr. Michelsens Institutt (CMI), 2016)
The purpose of this Country Evaluation Brief is to present relevant knowledge about donors’ development efforts in Mozambique. The brief systematises relevant findings from existing evaluations of development interventions in the country. The idea is to present the findings to the reader in a succinct and easily accessible format
Keywords: G - Mozambique / Moçambique; L - english / inglês; M - evaluation / avaliação

Reality checks in Mozambique: building better understanding of the dynamics of poverty and well-being. Final Report 2011-2015 - Tvedten, Inge; Tuominen, Minna; Rosário, Carmeliza (ORGUT Consulting AB, 2016)
A series of five “Reality Checks” will take place in the period 2011-2016, focussing on the dynamics of poverty and well-being with a particular focus on good governance, agriculture/climate and energy that are key sectors in Swedish development cooperation with Mozambique. Each Reality Check will be published in the form of one Annual Report and three Sub-Reports from each of the three selected study-sites (see ORGUTa 2011 for more details). More concretely, the “Reality Checks in Mozambique” are expected to: i) Inform the public discussion among key development actors on poverty reduction, especially in the province of Niassa; ii) Contribute to a better understanding of qualitative poverty monitoring methods in Mozambique; iii) Provide Sweden with relevant qualitative data on developments and results from its engagement in Mozambique and support further implementation of its programme in Niassa. The series of studies was initiated by an Inception Report published in August 2011 (ORGUT 2011a). Through that exercise, it was decided that the Reality Checks shall be based on fieldwork in three different Districts/Municipalities in the Province of Niassa that display variations in terms of geographical locations, access to public services and levels of poverty and well-being. The three areas selected were i); the Municipality of Cuamba; ii) the District of Lago and iii) the District of Majune (see Map 1). The 1 st Reality Check was carried out in 2011 in the form of three sub-reports (Orgut 2011 b,c,d) and the first Annual Report (Orgut 2011 e), and represent a baseline upon which the subsequent Reality Checks will build. This is the Annual Report for the 2 nd Reality Check, synthesising the main findings from the Cuamba, Lago and Majune sub-reports. In addition to pursuing the overall issue of the dynamics of poverty and well-being, this year’s reports have a thematic focus on governance.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Cuamba; GD - Lago; GD - Majune; GP - Niassa; L - english / inglês; M - evaluation / avaliação; agriculture / agricultura; gender / género; institutions / instituições; poverty / pobreza; private sector / setor privado

Reality checks in Mozambique: building better understanding of the dynamics of poverty and well-being. Annual Report, Year Three, 2013 – Agriculture, Climate and Employment - Tvedten, Inge; Rosário, Carmeliza; Tuominen, Minna; Samuel Jones (ORGUT Consulting AB, 2013)
A series of five “Reality Checks” will take place in the period 2011-2016, focussing on the dynamics of poverty and well-being with a particular focus on good governance, agriculture/climate and energy that are key sectors in Swedish development cooperation with Mozambique. Each Reality Check will be published in the form of one Annual Report and three Sub-Reports from each of the three selected study-sites (see ORGUTa 2011 for more details). More concretely, the “Reality Checks in Mozambique” are expected to: i) Inform the public discussion among key development actors on poverty reduction, especially in the province of Niassa; ii) Contribute to a better understanding of qualitative poverty monitoring methods in Mozambique; iii) Provide Sweden with relevant qualitative data on developments and results from its engagement in Mozambique and support further implementation of its programme in Niassa. The series of studies was initiated by an Inception Report published in August 2011 (ORGUT 2011a). Through that exercise, it was decided that the Reality Checks shall be based on fieldwork in three different Districts/Municipalities in the Province of Niassa that display variations in terms of geographical locations, access to public services and levels of poverty and well-being. The three areas selected were i); the Municipality of Cuamba; ii) the District of Lago and iii) the District of Majune (see Map 1). The 1 st Reality Check was carried out in 2011 in the form of three sub-reports (Orgut 2011 b,c,d) and the first Annual Report (Orgut 2011 e), and represent a baseline upon which the subsequent Reality Checks will build. This is the Annual Report for the 2 nd Reality Check, synthesising the main findings from the Cuamba, Lago and Majune sub-reports. In addition to pursuing the overall issue of the dynamics of poverty and well-being, this year’s reports have a thematic focus on governance.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Cuamba; GD - Lago; GD - Majune; GP - Niassa; L - english / inglês; M - evaluation / avaliação; agriculture / agricultura; institutions / instituições; poverty / pobreza

Support to Civil Society Engagement in Policy Dialogue - Ministry of Foreign Affairs of Denmark (Joint Evaluation, 2013)
This evaluation, the ‘Joint Evaluation of Support to Civil Society Engagement in Policy Dialogue’ was initiated by the Donor Group on Civil Society and Aid Effectiveness. Specifically it was commissioned by three Development Partners (DPs), ADC/Austria, Danida/Denmark and Sida/Sweden, which form the Management Group. A larger group of bilateral DPs support the evaluation through their participation as the international Reference Group. The evaluation took place between June 2011 and September 2012. The Evaluation Team was drawn from the consulting firm ITAD Ltd in the UK (lead firm), together with experts from COWI (Denmark) and experts from each of the three countries selected for the fieldwork, Bangladesh, Mozambique and Uganda. The purpose of this evaluation is lesson learning, to help DPs gain a better understanding of how best to support Civil Society Organisations (CSOs) in the area of policy dialogue. The findings will also have direct relevance to the CSOs in the three countries and the wider CSO community, as well as the Governments and local authorities interacting with Civil Society (CS) representatives. The evaluation focuses on: 1. How CSOs engage in policy dialogue and the relevance and effectiveness of their policy work; 2. the enabling environment, that is the enablers and barriers to CSO engagement; and 3. how different DP support strategies may influence CSOs’ ability to engage in policy dialogue, and how best the DPs might support CSO policy dialogue in the future.
Keywords: G - Mozambique / Moçambique; L - english / inglês; M - evaluation / avaliação; citizenship & participation / cidadania e participação; civil society / sociedade civil

Reality checks in Mozambique: building better understanding of the dynamics of poverty and well-being. Annual Report, Year One - Tvedten, Inge (ORGUT Consulting AB, 2012)
he Reality Checks are implemented 2011-2016 and each year field work is carried out in the Municipality of Cuamba, the District of Lago and the District of Majune in the Niassa Province. This is the Annual Report for Year One of the Reality Checks and aims at summarising the conclusions based on the findings from the field sub-report from each study location.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Cuamba; GD - Lago; GD - Majune; GP - Niassa; L - english / inglês; M - evaluation / avaliação; agriculture / agricultura; gender / género; poverty / pobreza

‘Opitanha’ Revisited Assessing the Implications of PARPA II in Rural Northern Mozambique 2006-2009 - Tvedten, Inge; Paulo, Margarida; Rosário, Carmeliza (Chr. Michelsen Institute, 2010)
This report is part of the efforts to monitor and evaluate the implications of Mozambique’s Poverty Reduction Strategy PARPA II (GdM 2005). Three qualitative and participatory studies have already been carried out in three different areas of the country: One in the District of Murrupula in Nampula Province (Tvedten, Paulo & Rosário 2006); one in four bairros in the capital Maputo (Paulo, Rosário & Tvedten 2007); and one in the district of Buzi in Sofala Province (Rosário, Tvedten & Paulo 2008). Each of these studies is to be followed up in order to ascertain changes in social relations and cultural perceptions of poverty and well-being, by visiting the same local administrations, the same communities and the same households after a period of three years. This report is the first in the series of the three such follow-up studies, with the Maputo and the Buzi studies planned for 2010 and 2011, respectively.
Keywords: *tagged; G - Mozambique / Moçambique; G - central / centro; G - north / norte; G - south / sul; GD - Murrupula; GP - Maputo; GP - Nampula; L - english / inglês; M - evaluation / avaliação; agriculture / agricultura; education / educação; poverty / pobreza; social inclusion & exclusion / inclusão e exclusão social; urbanization / urbanização